The cancer detectives [videorecording (DVD)] - Tempest, Gene; Winslow, Andia (PBS Distribution, 2024)
How one of the most impactful, lifesaving tests for women was created and popularized by a Greek immigrant and his wife, a famous Japanese-American illustrator who was detained in a WW2 internment camp, and a groundbreaking Black female surgeon. In the 1950's, survival rates from cancer of any kind were low. Damaging surgery and unsophisticated radiotherapy were the main treatments, assuming the disease was detected in time for anything to be done. Cervical cancer was often asymptomatic until it was well advanced, and by that time, it was often a death sentence.